Industrialisation, Finance, and Urbanisation in Africa - Oluwatosin A. Adeniyi; Oludele Folarin (African Governance and Development Institute (AGDI), 2023)
This study investigated two key questions: what is the impact of industrialisation on urbanisation in Africa? and to what extent does financial development affect this industrialisation- urbanisation nexus? To elicit answers to these questions, data from thirty-three (33) African countries over a period of twenty-eight (28) years were analysed using a dynamic panel estimator. The findings showed that industrialisation had positive and significant effects on urbanisation. Further, the study shows that financial development had a positive effect on urbanisation, although it lowers the positive effect of industrialisation on urbanisation. Hence, industrial policies, particularly those with marked job creation possibilities, should be accompanied by well-designed urban planning policies in order to sidestep the adverse socio-economicconsequences connected with the development of slums in urban areas.
Keywords: G2; L16; O18; N17; 330; Urbanisation; Industrialisation; Financial Development; Africa